Updates to Expected Yield Stress and Tensile Strength Ratios for Determination of Expected Member Capacity in the 2016 AISC Seismic Provisions - Liu, Judy (Engineering Journal, 2016)
The expected yield stress and expected tensile strength ratios for hollow structural sections (HSS), pipe, and steel reinforcement for steel-concrete composite construction have been updated for the 2016 AISC Seismic Provisions for Structural Steel Buildings. For HSS, each grade of steel, including the new ASTM A1085 specification, has its own Ry and Rt values. Expected yield stress and tensile strength ratios have also been defined for different grades of steel reinforcement. The revisions were based on analysis of mill test data for HSS and pipe from a number of producers and a comprehensive mill survey conducted by the Concrete Reinforcing Steel Institute (CRSI).